2021
DOI: 10.51985/zdvz6566
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Error in Juvenile Patients Presenting with Nystagmus at Tertiary Care Hospital of Karachi

Abstract: Objective: To evaluate the types of refractive errors in nystagmus patients among the age (5-15 years) patients. Study Design and Setting: An observational cross-sectional study was conducted at Pediatric department of Al-Ibrahim Eye Hospital, Karachi from June 2018 to March 2019. Methodology: A total of 55 patients (110 eyes) were selected from study setting. The protocol for examination for all patients were evaluated at the special clinic of Orthoptics includes the demographic data, educational status, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In contrast to our study, Perveen et al study showed that (42%) had myopic astigmatism as the most common refractive error then (30%) eyes had hyperopic astigmatism, 20 (18%) eyes had hyperopia and 11 (10%) eyes had myopia 15 .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our study, Perveen et al study showed that (42%) had myopic astigmatism as the most common refractive error then (30%) eyes had hyperopic astigmatism, 20 (18%) eyes had hyperopia and 11 (10%) eyes had myopia 15 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, in a study conducted in Karachi, there was no preponderance of hyperopia; this may be because the age bracket of the patients was 5 -15 years. 18 Visual delay was detected in a significantly high number (19.8%) of children, and interestingly, 42% of these children were hyperopic, while 21%had esotropia. Visually challenged infants with poor or absent accommodation with or without hyperopia must deal with blurred near vision.…”
Section: Discussionmentioning
confidence: 92%